Renal scarring is the most significant predictor of breakthrough febrile urinary tract infection in patients with simplex and duplex primary vesico-ureteral reflux. Issue 2 (April 2020) - Loukogeorgakis, Stavros P.; Burnand, Katherine; MacDonald, Alex; Wessely, Katherine; De Caluwe', Diane; Rahman, Nisha; Farrugia, Marie-Klaire
Summary: Introduction: The association of high-grade vesico-ureteral reflux (VUR) with renal dysplasia and/or scarring is well-established, and the combination of these factors has been shown to decrease the likelihood of VUR resolution. Other VUR parameters have similarly been shown to be associated with VUR non-resolution, including VUR grade and timing at cystography, associated urinary tract anatomical abnormalities, and bladder dysfunction. Objective: To establish independent risk factors that can predict symptomatic persistence of VUR. Design: This was a single-centre study (2011–2017) including consecutive prospectively collected patients with primary VUR on voiding cystourethrogram (VCUG). Patients with dilating VUR also underwent renography (dimercaptosuccinic acid [DMSA] or 99m-technetium mercaptoacetyltriglycine [ 99m Tc-MAG3]). All patients were initially managed medically with antibiotic prophylaxis. Primary outcome was febrile culture-positive breakthrough urinary tract infection (BT-UTI). Demographic parameters, as well as VUR grade, VUR timing at cystography, presence of ureteral anomaly, VUR index (VURx), and differential renal function (DRF) or scarring were analysed to determine independent predictors. Results: A total of 61 patients (41 male, of whom 7 circumcised at presentation) were studied. VUR was diagnosed following investigation of prenatal hydronephrosis in 37 patients (62%) and following a febrile UTI in 22 (37%). Median [range] follow-up period was 38 [12–84] months. Data from a total of 77 refluxing renal units (RUs) were used for analysis. Analysis of VCUG data demonstrated that high VURx might be a potential significant predictor of breakthrough UTI (RR: 1.7, 95% CI: 1.1–2.7, p < 0.05 vs low VURx) but this was not the case for individual VURx components. Renography data showed increased risk of breakthrough UTI in patients with renal scarring (relative risk (RR): 5.1, 95% confidence interval (CI: 2.0–10.7, p < 0.0001 vs no renal scarring), but not in patients with reduced DRF. Multivariate regression analysis revealed that renal scarring was the only significant risk factor for breakthrough UTI. VUR patients with renal scarring were three times more likely to develop breakthrough UTI (odds ratio (OR): 3.3, 95% CI: 1.4–7.4, p < 0.01). Discussion: Multiple factors have been shown to be significant predictors of radiological VUR resolution. Univariate analysis of these factors suggests that only scarring on DMSA and VURx are significant predictors of symptomatic non-resolution. On multivariate analysis, scarring on DMSA was the only significant predictive variable. This information will be useful in targeting investigation and treatment in susceptible patients and when counselling families. Conclusion: Renal scarring is the most significant risk factor for breakthrough UTI in primary VUR patients and could be used to determine those at risk of symptomatic VUR persistence. Summary Figure Urinary tract infection (UTI)-free survival in vesico-ureteral reflux (VUR) patients with (green/+) or without (red/-) renal scarring/dysplasia. ∗ p < 0.01. Summary Figure